Descent : a novel - Johnston, Tim, 1962- (Algonquin Books of Chapel Hill, 2015)
A girl vanishes "on a sunny, late-summer vacation morning" and thus begins a "family's harrowing journey down increasingly divergent and solitary paths, until all that continues to bind them to each other are the questions they can never bring themselves to ask: At what point does a family stop searching? At what point does a girl stop fighting for her life?"--